The information resources policy handbook research for the Information Age - Compaine, Benjamin M.; Read, William H. (MIT Press, 1999)
To understand the Information Age one must understand the concept of information as a resource. Like other basic resources, such as energy and materials, information resources are building blocks of society. But unlike energy and materials, they are far more abundant and versatile. Information resources include computers, telecommunications, the mass media, and financial services, all created or changed by the movement from analog to digital. This collection looks at the factors underlying digital technologies as well as the resulting public and strategic policy issues.
Keywords: Information resources management -- Handbooks, manuals, etc.; elektronické knihy; electronic books